EFEKTIVITAS PEMAKAIAN LENSA KONTAK LUNAK BAGI KENYAMANAN MATA DI OPTIK KOTA PADANG - Corina, Febry; Amir, Amril; Randi, Peni Okto (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
This study discusses the effectiveness of the use of soft contact lenses for eye comfort in the optical city of Padang. This study aims to: (1) test the effectiveness of wearing and maintaining soft contact lenses for eye comfort. (2) Know how to use and care for soft contact lenses. This type of research is a quasi-experimental. The population in this study were all patients who used soft contact lenses during the study. Sampling in this study used a total sampling technique. Data was collected through a questionnaire, then the data was submitted in accordance with the theory proposed at the library meeting. The data is discussed with the effectiveness test through pre and post data.